Neuropsychological and neurophysiological features of cognitive functions in patients with stage II Parkinson's disease - Aravitskaya, Dj. N. (Запорізький державний медичний університет, 2022)
The aim was to study the features of psycho-emotional and cognitive functions in patients with PD stage II using neuropsychological and neurophysiological examination.
Keywords: тези доповідей